Keeping Kids in Care: Reducing Administrative Burden in State Child Care Development Fund Policy. (12th June 2021) - Jenkins, Jade Marcus; Nguyen, Tutrang
Abstract: With limited federal requirements for block grants, states have developed very different welfare policies, often with onerous recertification or reporting requirements, creating barriers to continuous program enrollment. Examined through the framework of Administrative Burden, our study examines how changes to burdensome policies in states' Child Care Development Fund (CCDF) programs affect the length of children's continuous enrollment in child care through the CCDF program, known as subsidy "spells." We exploit state-level changes in three key policies during a 10-year period (2004–13) that capture administrative burden: (1) length of eligibility redetermination; (2) reporting requirements for income changes; and (3) grace period for care before termination. Using state fixed effects analyses in a sample of 38 states using data from the Administration for Children and Families and multiple other sources, we find that administrative burdens meaningfully and robustly affect continuous enrollment in CCDF; switching to a 12-month redetermination period, as required 2014 Child Care and Development Block Grant reauthorization, increases children's continuous enrollment in CCDF care (i.e., state median spell length) by 30%. In contrast, requiring all changes in family income to be reported while enrolled in CCDF decreases spell length by 7%. Results underscore the importance of reducing administrative burdens related to compliance costs to better support low-income citizens, especially those with young children, and improve child development.